2019
DOI: 10.1080/19401493.2018.1561754
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and pitfalls of using building performance simulation in explorative R&D contexts

Abstract: One of the promising use cases of building performance simulation (BPS) is its role as a virtual laboratory in research and development (R&D) projects that aim to bring innovative building components from initial idea towards market introduction. By facilitating what-if explorations and whole-building insights, BPS can create complementary value, alongside actual experiments. However, explorative R&D projects tend to be rather erratic and are more ill-defined than typical BPS tasks. This raises several issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Several modelling studies have shown that energy performance simulations can quite accurately depict the energy consumption of buildings, and can have a significant impact on designing new materials to optimize the energy performance [28][29][30]. Nevertheless, it is important that modeling parameters are defined and documented precisely, to prevent pitfalls and to ensure comparability between the studied systems, as well as between different studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several modelling studies have shown that energy performance simulations can quite accurately depict the energy consumption of buildings, and can have a significant impact on designing new materials to optimize the energy performance [28][29][30]. Nevertheless, it is important that modeling parameters are defined and documented precisely, to prevent pitfalls and to ensure comparability between the studied systems, as well as between different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have deducted several other parameters that are important to ensure comparability and convey the full energy reduction potential of thermochromic windows to the glazing industry and the general public: i) when thermochromic windows are compared to commercially available energy-efficient glazing solutions, systems with similar visible transmission have to be compared; ii) for better comparison with commercial products, G and U-values [31,32] need to be reported; iii) to grasp the full potential of thermochromic windows, the switching temperature has to be optimized for each system individually. Further, most modeling studies on thermochromic windows focus on the energy reduction potential in office buildings [23- Several modelling studies have shown that energy performance simulations can quite accurately depict the energy consumption of buildings, and can have a significant impact on designing new materials to optimize the energy performance [28][29][30]. Nevertheless, it is important that modeling parameters are defined and documented precisely, to prevent pitfalls and to ensure comparability between the studied systems, as well as between different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the amount of energy consumption and designing the HVAC system is the most common usage of simulations. In some studies IEQ aspects are considered on the basis of temperature set points and ventilation rate (Loonen et al , 2015). There are different developed computational models for simulating each IEQ aspect (Zhang and Chen, 2009; Hensen and Lamberts, 2011; Vorländer, 2013).…”
Section: Human Behavior and Building Energy Consumptionmentioning
confidence: 99%
“…control) beyond what is possible by simple scripting approaches. In design practice, this often creates a need for workarounds (Loonen, de Klijn-Chevalerias, and Hensen 2019) that quite often result in unintended and undesirable modelling artifacts.…”
Section: Introductionmentioning
confidence: 99%